Pengaruh Harga Minyak Dunia dan Belanja Infrastruktur terhadap Keseimbangan Anggaran Pemerintah Indonesia 2015-2024 - Primasari Fitria; Syaputri, Ayu Geby Gisela; Muhammad Bahrul Ulum (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to examine the extent to which World Oil Prices and Infrastructure Spending influence Indonesia's Budget Balance in 2015-2024. The data used in this study are secondary data from 2015-2024. The analysis method used is multiple linear regression analysis. The analysis results indicate that crude oil prices and infrastructure expenditure simultaneously have a significant effect on the Budget Balance, with an F-value of 5.720 and a significance level of 0.013 < 0.015. Partially, infrastructure expenditure has a significant impact on the state budget deficit, with a coefficient of β = 0.456 and p < 0.05, whereas crude oil prices do not have a significant effect (β = -0.106, p = 0.28). This is due to fluctuations in crude oil prices that do not always align with the continuously increasing trend of the state budget deficit each year. Infrastructure expenditure plays a crucial role in supporting economic growth, prompting the government to increase capital spending for development.